Employee Perceptions, Proximity Bias, and Performance Evaluation in Hybrid Work: The Quasi-Moderating Role of Work Flexibility and Virtual Interaction - Ryan Saputra Alam; Nur Imam Saifuloh; Noviarti; Darmianti Razak (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The development of hybrid work systems has brought about new dynamics in employee performance appraisal. This study aims to analyze the effect of employee perceptions of hybrid work (PK) and proximity bias (PB) on performance evaluation (EK), with work flexibility and virtual interaction (FI) as moderating and mediating variables. The study used three regression models, namely Model 1 (direct effect), Model 2(additional moderation), and Model 3 (interaction test), followed by a mediation test. The results showed that in Model 1,PK (0.437) and PB (0.369) had a positive and significant effect on EK. In Model 2, the addition of the FI variable produced a positive and significant effect on EK (PK = 0.110; PB = 0.290; FI = 0.440). Model 3 found that PK,PB, and FI remained positively and significantly influential (PK = 0.140; PB = 0.264; FI= 0.503), with the interaction PKFI strengthening the effect of PK on EK (0.346),while the interaction PBFI weakens the effect of PK on EK(-0.363). The mediation test shows that FI acts as a quasi-moderator and mediator in the relationship between PK and PB on EK.These findings confirm that in the context of hybrid work, work flexibility and virtual interaction not only clarify performance evaluation but can also reduce the effect of physical presence bias(proximity bias). This research has implications for human resource management strategies in designing fair and productive hybrid work policies.